EVALUATION OF GENOTYPE × ENVIRONMENT INTERACTION FOR ESSENTIAL OIL YIELD AND ITS RELATED TRAITS FOR IDENTIFICATION OF SUITABLE CULTIVARS IN CITRONELLA (CYMBOPOGON WINTERIANUS JOWITT.) IN MEGHALAYA, INDIA - P.K. MALLIKARJUN; S.K.NOREN; N.B.SINGH; MOHAN LAL; A. K. SINGH; N. J. SINGH; G.SHARMA (The Bioscan, 2021)
Cymbopogon winterianus Jowitt. is an important aromatic crop, which provides essential oil upon distillation, however this crop is extensively influenced by various environmental factors. Therefore, the present investigation was undertaken to evaluate the stability of Citronella genotypes over four seasons. The outcome of AMMI ANOVA, studied using principal component analysis (PC1), represented 69.79 % for plant height, 76.31 % for number of leaves per clump, 73.61 % for fresh biomass yield per plot and 61.74 % for essential oil yield of GEI sum of squares percentage. High oil yielding and widely stable genotypes were identified almost similar by Eberhart and Russell (1966) and AMMI model analysis. Four genotypes were constituted to be high yielding and stable for fresh biomass yield. Bio-13 (10.27 ml/kg) and Mandakini (9.92 ml/kg) genotypes were registered as high oil yielding and stable. Whereas, JC-4 (9.90 ml/kg) showed better adaptable genotype for essential oil yield. The results revealed consistent performance of these genotypes across the seasons due to their ability to tolerate wide environmental conditions of different seasons. These genotypes can be feasibly utilized in future breeding programmes in Citronella on the basis of high oil yield and stable nature.